Cumulative effect of loneliness and social isolation on health outcomes among older adults. (3rd July 2022) - Barnes, Timothy L.; MacLeod, Stephanie; Tkatch, Rifky; Ahuja, Manik; Albright, Laurie; Schaeffer, James A.; Yeh, Charlotte S.
Abstract: Objectives: Loneliness and social isolation are described similarly yet are distinct constructs. Numerous studies have examined each construct separately; however, less effort has been dedicated to exploring the impacts in combination. This study sought to describe the cumulative effects on late-life health outcomes. Method: Survey data collected in 2018–2019 of a randomly sampled population of US older adults, age 65+, were utilized ( N  = 6, 994). Survey measures included loneliness and social isolation using the UCLA-3 Loneliness Scale and Social Network Index. Participants were grouped into four categories based on overlap. Groups were lonely only, socially isolated only, both lonely and socially isolated, or neither. Bivariate and adjusted associations were examined. Results: Among participants (mean age = 76.5 years), 9.8% ( n  = 684) were considered lonely only, 20.6% ( n  = 1, 439) socially isolated only, 9.1% ( n  = 639) both lonely and socially isolated, and 60.5% ( n  = 4, 232) neither. Those considered both lonely and socially isolated were more likely to be older, female, less healthy, depressed, with lower quality of life and greater medical costs in bivariate analyses. In adjusted results, participants who were both lonely and socially isolated had significantly higher rates of ER visits and marginally higher medical costs. Conclusion: Results demonstrate cumulative effects of these constructs among older adults. Findings not only fill a gap in research exploring the impacts of loneliness and social isolation later in life, but also confirm the need for approaches targeting older adults who are both lonely and socially isolated. As the COVID-19 pandemic continues, this priority will continue to be urgent for older adults.